3D numerical simulation of initiation, propagation and coalescence of cracks using the extended non-ordinary state-based peridynamics. (June 2019) - Shou, Yundong; Zhou, Xiaoping; Berto, Filippo
Highlights: An extended non-ordinary state-based peridynamics is proposed. The numerical specimens containing 3D pre-existing flaws are simulated. Failure mode and crack coalescence process of numerical specimens are obtained. Abstract: An extended non-ordinary state-based peridynamics is proposed to investigate the initiation, propagation and coalescence of 3D pre-existing flaws in PMMA specimen subjected to uniaxial compressive loads. The maximum principal stress criterion and twin-shear strength criterion are introduced to the extended non-ordinary state-based peridynamics. A program code is compiled to demonstrate the validity of the extended non-ordinary state-based peridynamics. In the present study, the numerical specimens of PMMA containing different types of three-dimensional pre-existing flaws under uniaxial compression are simulated to prove the ability of the proposed numerical method to model the propagation and coalescence of 3D cracks. The axial stress versus axial strain curves are obtained using the proposed numerical method as well as the ultimate failure mode and crack coalescence process. The present numerical results are in good agreement with the previous experimental data.